ROLE OF ENDOGENOUS FLUIDS IN THE FORMATION OF CARBON-BEARING ROCKS IN THE GEOLOGICAL SECTION OF THE OIL-AND-GAS PROVINCES - Gottikh R.P.; Pisotsky B.I.; Zhuravlev D.Z. (My University, 2007)
The base of practically all oil-and-gas basins is composed of rocks with anomalous geochemical characteristics: elevated contents of organic matter (OM) and metals. Most researchers suggest that periodical accumulation of such specific sequences was caused by large-scale global basaltic volcanism, which led to catastrophes in the history of organic life and simultaneous accumulation of significant amounts of trace elements in sediments. The aim of this study was to establish the contribution of deep-seated emanations in the formation of the Frasnian (Upper Devonian) domanik carbon-bearing rocks within the South Tatar dome of the Russian Plate.
Keywords: Paleozoic::Devonian::Upper::Frasnian; Палеозой::Девонская::Верхний::Франский